Teacher Stroke as a Positive Interpersonal Behavior on English as a Foreign Language Learners' Success and Enthusiasm - Song, Zhe (Frontiers in Psychology, 2021)
In language learning contexts, teacher-student interactions are regarded pivotal for their impact on learners’ education and their academic journey. To help learners succeed, teachers may employ numerous ways to develop this interpersonal relationship, one of which is teacher stroke that is called teacher praise, as well. Interpersonal skills, societal encouragement, and stroking manners, the respect, consideration, or reaction that an individual provides for each other can uphold such a connection and affect students’ enthusiasm. To this end, this review paper makes an effort to review the prominence of teacher stroke in the process of learning in the classroom and illustrate their relationship and impact on learners’ enthusiasm and success. Furthermore, this review contributes to the body of dominant literature, and suggestions and recommendations have been presented for language teaching stakeholders in the educational setting.